Penguatan Semangat dan Motivasi Berwirausaha UMKM Sagu di Kelurahan Guraping Kecamatan Oba Utara Kota Tidore Kepulauan - Fadhliah M. Alhadar; Marwan Marwan; E.Ida Hidayanti; Musdar Muhammad (Jurnal Pengabdian Masyarakat, 2025)
This community service program (PKM) aims to increase the entrepreneurial spirit and motivation of sago MSME actors in Guraping Village. The methods used are Socialization, Training, and Mentoring and Evaluation, which include business management materials, technology utilization, effective and efficient marketing strategies, and introduction to financing sources. This PKM activity was held on May 22, 2025 at the Guraping Village Meeting Building and was attended by 30 sago business actors.The results of the service show that this program is very important because entrepreneurial motivation is the main foundation for the success of MSMEs, and the use of digital technology is key in the development of MSMEs, especially in more prospective marketing, reducing promotional costs, and reaching the global market. However, there are still many MSME actors who have not fully utilized digital marketing. Through this activity, it is hoped that an ecosystem can be created that supports the sustainability of MSMEs, opens up opportunities for progress, and encourages community independence.